Ecological impact of Oued Fez canalisation Morocco on waterbirds biodiversity - ISSAOUI, Ayoub EL; BOUHADDIOUI, Abderrahim; BAHHOU, Jamila (Edelweiss Applied Science and Technology, 2025)
The Oued Fez River crosses northern Fez and historically maintained a permanent marsh that supported both resident and migratory waterbird communities. In 2024, the Sebou Water Basin Agency implemented river-channeling operations to control Pistia stratiotes, an invasive aquatic plant. These interventions altered the hydrological regime and resulted in the complete drying of the wetland area. To assess the ecological consequences of these developments, monthly waterbird surveys were conducted over a three-year period (2022–2024), covering conditions before and after the works. Results indicate a marked decline in avifaunal diversity, with total numbers decreasing from 2,910 individuals in 2022 to 756 in 2024, and species richness falling from 66 to 28, mainly affecting migratory species. A Student’s t-test confirmed a statistically significant difference between the two periods, suggesting that the observed changes are attributable to habitat degradation rather than random variation. The loss of wetland habitat, disruption of hydrological dynamics, and reduction of suitable wintering and feeding areas appear to be the primary drivers of this decline. The study underscores the need for integrated ecological management to balance hydraulic development objectives with the conservation of avian biodiversity.